Uncertainty quantification and global sensitivity analysis of turbulence model closure coefficients for sheet cavity flow around a hydrofoil - Simone Romani; Mitja Morgut; Lucia Parussini; Marzio Piller (Brodogradnja)
This paper presents the uncertainty quantification and sensitivity analysis of the standard k-ɛ turbulence model applied to the numerical prediction of the non-cavitating and cavitating flow around a 2D NACA66MOD hydrofoil. The turbulence model parameters are treated as epistemic uncertain variables, and the forward propagation of uncertainty is evaluated using the non-intrusive polynomial chaos approach. The required simulations are performed using a commercial CFD solver. The Sobol indices are used to rank the relative contribution of closure coefficients to the total uncertainty in the output quantities. For the considered case, the ranking of the model parameters is not influenced by the presence of the sheet cavity flow, while it varies with respect to the considered output quantity.